Economic costs and benefits of allocating forest land for industrial tree plantation development in Indonesia - Maturana, J. (2005)
The allocation of large areas of State owned forest land for the development of Industrial Timber Plantations (HTI) in Indonesia has been very important in supporting the economically-important pulp and paper industry. This allocation resulted in totally clearing vast areas of forests already logged for their prime timber and the elimination of the many environmental and social benefits these areas provide. This CIFOR working paper analyzes the economic costs and benefits of the allocation of nearly 1.4 million hectares of logged-over forests to five large pulp-plantation companies in Sumatra. The results and conclusions may be particularly relevant for future forestry policy in Indonesia.